ANALISIS PENERAPAN PAJAK PENGHASILAN FINAL PASAL 4 AYAT 2 PADA PERUSAHAAN JASA KONSTRUKSI PT. CONSPEC PERTAMA INDONESIA - Sri Setia Ningsih; Sari Yulianti; Erion Erion; Lestari Adhi Widyowati; Gunawan Raspatty (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The purpose of this research is to find out how the regulations of Tax Law Number 36 of 2008 concerning reporting and calculating final income tax on construction services at